Chromium(0) and Molydenum(0) Complexes with a Pyridyl-Mesoionic Carbene Ligand: Structural, (Spectro)electrochemical, Photochemical, and Theoretical Investigations - Bens, Tobias (2020)
This work reports on the synthesis and in-depth electrochemical and photochemical characterization of two chromium(0) and molydenum(0) metal complexes with bidentate pyridyl-mesoionic carbene (MIC) ligands of the 1,2,3-triazol-5-ylidene type and carbonyl coligands. Metal complexes with MIC ligands have turned out to have very promising electrocatalytic and photochemical properties, but examples of MIC-containing complexes with early-transition-metal centers remain extremely rare. The electrochemistry of these new MIC complexes was studied by cyclic voltammetry and especially spectroelectrochemistry in the IR region consistent with a mainly metal-centered oxidation, which is fully reversible in the case of the chromium(0) complex. At the same time, the two reduction steps are predominantly ligand-centered according to the observed near-IR absorbance, with the first reduction step being reversible for both systems. The results of the electron paramagnetic resonance studies on the oxidized and reduced species confirm the IR spectroelectrochemistry experiments. The photochemical reactivity of the complexes with a series of organic ligands was investigated by time-resolved (step-scan) Fourier transform infrared (FTIR) spectroscopy. Interestingly, the photoreactions in pyridine and acetonitrile are fully reversible with a slow dark reverse reaction back to the educt species over minutes and even hours, depending on the metal center and reagent. This reversible behavior is in contrast to the expected loss of one or several CO ligands known from related homoleptic as well as heteroleptic M(CO)4L2 α-diimine transition-metal complexes.